The Increasing Effectiveness of Musical Education by Popular Music - Rauduvaitė, Asta (Pedagogika, 2013)
The article investigates the opportunities of musical education effectiveness increase by fostering attitudes of moral values for young schoolchildren by integrating a popular music. The attitudes of moral values are based on the context of pedagogical thoughts and theories of psychological development; following the research results the relations and opportunities of improvement of schoolchildren musical activities and attitudes of moral values are being discussed. The importance of values in the process of education is obvious for most of the education policy-makers and practicians of different countries. The attitudes of values are a priority goal in strategic documents and respond new challenges for education, i.e. rapid changes of country’s social and economic areas as well as growing opportunities for implementing educational innovations. Therefore, while raising educational goals, it is important to consider all the factors which could influence them, as well as maintain a schoolchild’s relation with the perceived reality. In this context primary musical education with it’s attractive forms of activities while integrating popular music, could contribute to the development for the integral educational process of a schoolchild‘s attitudes of moral values, competences, knowledge and perception. The relevance of the issue is young schoolchildren interest in popular music and controversial attitudes towards it’s influence. Looking to modern personal and professional ambitions, considering the attractiveness of popular music, which corresponds the demands of schoolchildren, the problem of modern music pedagogy is young children’s education of attitudes of moral values by actively integrating a popular music. The analysis of scientific literature reveals that popular music is a distinctive sociocultural factor, a source of internal force expression; therefore, it’s involvement to the process of education could satisfy the demands of schoolchildren self-expression and self-education, stimulates it’s value based importance. Thus, in the context of pedagogical thoughts and theories of psychological development, the effectiveness of musical education could be increased in the following way: an introductory teacher’s speech, to familiarize schoolchildren with the perception of music composition / musical activity → an identification of music intonations, an experience of music → an outline of musical experience by telling a perceived personal meaning → modelling of virtual situation of moral content → decision making → evaluation → an appropriate perception and etc. These are the factors that positively enhance a schoolchild‘s maturity of musical and value based perception. The research results reveal that a method of personal meaning is accepted and efficient for education of attitudes of moral values by popular music of young schoolchildren. The application of the idea of personal meaningfulness for primary musical education, stimulates a child’s reflections and perception of relation between spiritual feelings and thoughts. A method of personal meaning reveals not only an individuality of knowledge, but also a perceivers position, his axiological attitude.